2010
DOI: 10.1021/ol102179u
|View full text |Cite
|
Sign up to set email alerts
|

Psiguadials A and B, Two Novel Meroterpenoids with Unusual Skeletons from the Leaves of Psidium guajava

Abstract: Psiguadials A (1) and B (2), two novel sesquiterpenoid-diphenylmethane meroterpenoids with unusual skeletons, along with a pair of known epimers, psidial A (3) and guajadial (4), were isolated from the leaves of Psidium guajava. Their structures with absolute configurations were elucidated by means of NMR, X-ray diffraction, and quantum chemical CD calculation. Compounds 1, 2, and 4 exhibited potent inhibitory effects on the growth of human hepatoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 16 publications
2
65
0
1
Order By: Relevance
“…In a previous study, an ethanolic extract from the same plant part had been reported to display activity against Trypanosoma b. brucei (Adeyemi et al, 2009). Previous phytochemical studies revealed the presence of saponins, alkaloids, steroids and/or triterpenes, flavonoids, phenolic acids and tannins in Alchornea cordifolia leaves (Kambu, 1990;Lamikanra et al, 1990;Tona et al, 1998;Banzouzi et al, 2002;Mavar Manga et al, 2004); Scorodophloeus zenkeri stem bark contains flavonoids and tannins (Ngono, 1999; tannins, terpenes, steroids and alkaloids are present in Isolona hexaloba stem bark (Cabalion, 1977;Hocquemiller et al, 1984); xanthones, anthrone derivatives, steroids, terpenes, alkaloids, coumarins, flavonoids, anthraquinones and tannins in Harugana madagascariensis stem bark (Linuma et al, 1995;Kouam et al, 2005); saponins, tannins, anthraquinones, alkaloids, steroids, triterpenes, flavonoids in Musanga cecropioides stem bark (Adeneye et al, 2006); tannins, saponins, anthraquinones, alkaloids, flavonoids, terpenes and steroids in Ocimum gratissimum leaves (Ijeh et al, 2004;Tchoumbougnang et al, 2005;Ueda-Nakamura et al, 2006;Amadi et al, 2010); amide alkaloids, terpenes, lignans and sterols in Psidium guineese stem bark (Adesina et al, 2002); flavonoids, tannins, terpenes and steroids in Psidium guajava leaves (Kambu, 1990;Tona et al, 1998;Metwally et al, 2010;Shao et al, 2010); triterpenoid glycosides, coumarins, flavonoids and tannins were detected in Tetrapleura tetraptera fruit (Maillard et al, 1992). Seven extracts were active against one of the selected protozoa (5 < IC 50 < 10 g/ml).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, an ethanolic extract from the same plant part had been reported to display activity against Trypanosoma b. brucei (Adeyemi et al, 2009). Previous phytochemical studies revealed the presence of saponins, alkaloids, steroids and/or triterpenes, flavonoids, phenolic acids and tannins in Alchornea cordifolia leaves (Kambu, 1990;Lamikanra et al, 1990;Tona et al, 1998;Banzouzi et al, 2002;Mavar Manga et al, 2004); Scorodophloeus zenkeri stem bark contains flavonoids and tannins (Ngono, 1999; tannins, terpenes, steroids and alkaloids are present in Isolona hexaloba stem bark (Cabalion, 1977;Hocquemiller et al, 1984); xanthones, anthrone derivatives, steroids, terpenes, alkaloids, coumarins, flavonoids, anthraquinones and tannins in Harugana madagascariensis stem bark (Linuma et al, 1995;Kouam et al, 2005); saponins, tannins, anthraquinones, alkaloids, steroids, triterpenes, flavonoids in Musanga cecropioides stem bark (Adeneye et al, 2006); tannins, saponins, anthraquinones, alkaloids, flavonoids, terpenes and steroids in Ocimum gratissimum leaves (Ijeh et al, 2004;Tchoumbougnang et al, 2005;Ueda-Nakamura et al, 2006;Amadi et al, 2010); amide alkaloids, terpenes, lignans and sterols in Psidium guineese stem bark (Adesina et al, 2002); flavonoids, tannins, terpenes and steroids in Psidium guajava leaves (Kambu, 1990;Tona et al, 1998;Metwally et al, 2010;Shao et al, 2010); triterpenoid glycosides, coumarins, flavonoids and tannins were detected in Tetrapleura tetraptera fruit (Maillard et al, 1992). Seven extracts were active against one of the selected protozoa (5 < IC 50 < 10 g/ml).…”
Section: Resultsmentioning
confidence: 99%
“…The 1D NMR spectra of 3 (Tables 1 and 2) exhibited most of the structural features found in psiguadial A ( 16 ) 9 , a known globulane-based Psidium meroterpenoid featuring a rare oxocane ring junction, except that a methylene ( δ C 36.6, C-2), an oxygenated quaternary carbon ( δ C 104.1, C-1) and an upfielded methine ( δ C 39.9, C-10) in 16 were replaced by a oxygenated methine ( δ C 85.5, C-2) and a tetra-subsitituted double bond ( δ C 138.2 and 136.0, C-1 and C-10) in 3 . This indicated that the oxygen bridge started from C-1 in 16 was migrated to C-2 with the formation of Δ 1(10) in 3 , which was further confirmed by the HMBC correlations (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…So far more than 100 phloroglucinol-coupled terpenoids have been reported 11, 18 , and their intriguing structures and important biological activities have attracted broad interest from both natural products and synthetic chemists over the last half century 5, 1924 . For instance, psiguadials A, C, and D 9, 10 , hyperjapones A–E 16 , and hyperjaponols A and C 17 with novel skeletons and appealing pharmacological activities (e.g., antitumor and antiviral properties) have been synthesized by several groups 25, 26 . Psidium meroterpenoids are a subgroup of this compound class, which are exclusively reported from the species Psidium guajava .…”
Section: Introductionmentioning
confidence: 99%
“…14 To date, the calculated experimental electronic circular dichroism (ECD) spectral data have been successfully utilized to determine the absolute configuration of complex naturally occurring compounds (e.g. sorbiterrin A, 18 psiguadials, 19 and discorhabdins 20 ). To further determine the absolute configuration of compounds 1–3 , a computational approach was applied, and the simulated ECD curves were then overlaid with the experimental CD spectra for comparison.…”
Section: Resultsmentioning
confidence: 99%